Mosque-Based Islamic Social Enterprise: A New ‎Approach to Mosque Management ‎Transformation - Fahmi, Rizqi Anfanni; Zulhamdi, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2023)
This paper explores the potential of Mosque-Based Islamic Social Enterprise (MBISE) as a new approach to mosque management transformation. As a religious entity that relies on donations, mosques often experience stagnation due to traditional management. Transformation is necessary to avoid dependence on donations to achieve the mosque's goals. The study examines the practices of MBISE in Indonesia, focusing on mosque business units. This paper used a mixed method approach by conducting a literature study based on online news and articles in scientific journals focusing on the mosque business unit as a representative of MBISE. Collected data were analyzed using content analysis techniques. The results show that at least 61 mosques have business units. More than 50% of the mosques are in the Java region. Most business is the rental of mosque assets such as halls, mosque courtyards, and shops. The largest source of funds is gathered from donations used as capital for business units (infak). The significant impact felt is the increased independence of the mosque with a source of income other than donations. Another widely enjoyed impact is the implementation of community empowerment around the mosque. The study shows that mosque business units indicate significant characteristics with the Islamic Social Enterprise concept called Mosque-Based Islamic Social Enterprise. This study contributes as a reference for the development of nonprofit organizations, especially mosques, so they can use congregational donations for activities that can multiply mosque income and support the achievement of mosque prosperity through mosque business units.